2023
DOI: 10.3389/fmicb.2023.1236368
|View full text |Cite
|
Sign up to set email alerts
|

Microbial proteases and their applications

Peng Song,
Xue Zhang,
Shuhua Wang
et al.

Abstract: Proteases (proteinases or peptidases) are a class of hydrolases that cleave peptide chains in proteins. Endopeptidases are a type of protease that hydrolyze the internal peptide bonds of proteins, forming shorter peptides; exopeptidases hydrolyze the terminal peptide bonds from the C-terminal or N-terminal, forming free amino acids. Microbial proteases are a popular instrument in many industrial applications. In this review, the classification, detection, identification, and sources of microbial proteases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 354 publications
0
4
0
Order By: Relevance
“…Intriguingly, our results underscore that TSB plays a pivotal role in facilitating the growth advantage of salt-tolerant peanuts in salt-stressed environments. Furthermore, we observed that genes related to amino acid metabolic pathways were significantly upregulated in peanuts treated with TSB under salt stress ( Figure 8A ), potentially aiding in preserving protein reserves in peanuts ( Ahmed et al, 2022 ; Song et al, 2023 ). Similarly, pathways such as glutathione metabolism, ascorbate, and aldarate metabolism exhibited upregulation in response to TSB treatment ( Figures 8A , B ).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, our results underscore that TSB plays a pivotal role in facilitating the growth advantage of salt-tolerant peanuts in salt-stressed environments. Furthermore, we observed that genes related to amino acid metabolic pathways were significantly upregulated in peanuts treated with TSB under salt stress ( Figure 8A ), potentially aiding in preserving protein reserves in peanuts ( Ahmed et al, 2022 ; Song et al, 2023 ). Similarly, pathways such as glutathione metabolism, ascorbate, and aldarate metabolism exhibited upregulation in response to TSB treatment ( Figures 8A , B ).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of protein digestibility is crucial for nutritional assessment in terms of the quality and bioavailability of feed products. Therefore, fermentation enhances in vitro protein digestibility possibly by Bacillus licheniformis proteolytic activity that can target plant-based proteins, thereby promoting hydrolysis, protein modification [70][71][72], and remediation of anti-nutritional factors such as trypsin inhibitors [19]. Some studies using lactic bacteria achieved 65-79% IVPD in hemp [73].…”
Section: Discussionmentioning
confidence: 99%
“…The inoculated plates were incubated at 30 • C for 4 to 5 days. Yeasts showing a clear zone around the colonies were selected and, considered protease-positive [7,25].…”
Section: Sampling and Yeast Strains Isolationmentioning
confidence: 99%
“…Protease enzymes degrade proteins at different sites [5]. Proteases within clans and families can be classified as asparagine proteases, aspartic proteases, cysteine proteases, glutamic proteases, mixed proteases, metalloproteases, threonine proteases, serine proteases, or unknown proteases based on these phylogenetic relationships and mechanisms of action [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation